The tale of Despereaux being the story of a mouse, a princess, some soup, and a spool of thread - DiCamillo, Kate (Scholastic, 2003)
The adventures of Desperaux Tilling, a small mouse of unusual talents, the princess that he loves, the servant girl who longs to be a princess, and a devious rat determined to bring them all to ruin.